Construction of MOFs nanoplatform with pH-triggered release of protocatechuic acid for intervertebral disc degeneration therapy. (January 2023) - Ding, Hong; Zhang, Xiang; Liu, Zheng; Wang, Juehan; Zhu, Ce; Chen, Qian; Huang, Yong; Ai, Youwei; Wu, Ruibang; Feng, Ganjun; Zhang, Li; Liu, Limin
Graphical abstract: Highlights: A MOFs-based intelligent nanoplatform with pH-triggered release of protocatechuic acid was constructed. The released rate of protocatechuic acid was adaptive to the degree of disc degeneration. The MOFs nanoplatform effectively delayed the degeneration process in rat disc degeneration model. Abstract: Lower back pain is a significant contributor to disability and incapacity in adults. Up to 40 % of lower back pain is considered to be caused primarily by disc degeneration. The pH value in the intervertebral disc (IVD) usually decreases with the progression of degeneration, which can act as an initiator to trigger the release of drugs precisely for inhibiting the intervertebral disc degeneration (IDD). Herein, we fabricated a pH-responsive metal organic framework (MOF) to load anti-inflammatory protocatechuic acid (PCA), followed by the encapsulation of hyaluronic acid (HA), the final product was abbreviated as MOF@PH. The results showed that the acidic microenvironment could trigger drug release from MOF@PH featured by an increasing release proportion with pH decreasing. The cell assessment indicated that MOF@PH could suppress the inflammatory response of the nucleus pulposus significantly, downregulate the expression of related inflammatory markers (IL-6, ROS, NLRP-3 etc.) and promote the expression of nucleus pulposus specific markers. The administration of MOF@PH in rat disc degeneration model was proven able to effectively delay the degeneration process. The pH-sensitive MOF@PH may offer an effective strategy to precisely treat the IDD with desired therapeutic effects.